Identification of Microplastics in Manggaba'i Fish (Glossogobius Giuris) in Limboto - Mohamad, Humaira; Jahja, Mohamad; Demulawa, Meilan (Peneliti.net, 2024)
Manggaba'i fish (Glossogobius giuris) is one of the important commercial fish species in Lake Limboto. Manggaba'i fish (Glossogobius giuris) is a vertebrate animal and is included in the demersal fish class. Human activities and the environment can influence the distribution and abundance of microplastics. This study was conducted to identify microplastics in manggaba'i fish (Glossogobius giuris). The aim is to determine the physical properties of microplastics based on the shape, color, and amount of Manggaba'i fish in Lake Limboto. Based on the results of the study and discussion regarding the physical characteristics of microplastics contained in the digestive system of manggaba'i fish in Lake Limboto, it can be concluded that the identification of microplastics in the digestive system of manggaba'i fish was found to be all in the form of fibers with a size of (10-12cm) black, and a size of (12.5-14cm) blue, red, and black.